2018
DOI: 10.1016/j.aop.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

How to understand the tunneling in attosecond experiment?

Abstract: The measurement of the tunneling time (T-time) in today's attosecond and strong field (low-frequency) experiments, despite its controversial discussion, offers a fruitful opportunity to understand time measurement and the time in quantum mechanics. In addition, as we will see in this work, a related controversial issue is the particulate nature of the radiation. Different models used to calculate the T-time will be discussed in this work in relation to my model of real T-time, Phys. Rev. 92, 052118 (2015), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 117 publications
(283 reference statements)
3
19
0
Order By: Relevance
“…, hence nothing happens, i.e. the electron remains in its ground state undisturbed, which shows that our model is consistent, for details see [6,10,11]. It is worthwhile to mention that Chang et al [37] found a better estimation of the atomic field strength, it is slightly larger than the estimation of Augst et al [31] ( F Fa a Cha Aug ), which is used in our work.…”
Section: The Tunneling Timesupporting
confidence: 78%
See 4 more Smart Citations
“…, hence nothing happens, i.e. the electron remains in its ground state undisturbed, which shows that our model is consistent, for details see [6,10,11]. It is worthwhile to mention that Chang et al [37] found a better estimation of the atomic field strength, it is slightly larger than the estimation of Augst et al [31] ( F Fa a Cha Aug ), which is used in our work.…”
Section: The Tunneling Timesupporting
confidence: 78%
“…In [10] it was shown that our tunneling model (section 2) in the attosecond experiments [5] is intriguingly similar to this Gedanken experiment, where the former can be seen as a realization to the later. And as mentioned, the agreement of the model with the experimental result of [5], is impressively good, see [6,10].…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations